MODERN TRAINING STRATEGIES USED IN E-LEARNING - Vali ILIE; Mihaela Aurelia ȘTEFAN (Universitaria Publishing House, Craiova, 2022)
The study focuses on the role of e-learning in the training process against the background of the digitalization of education. We aim to analyze the impact of elearning on the school performance of the students. Starting from a comparative analysis between traditional learning and e-learning, we focus on the training strategies that capitalize on the new information and communication technologies. In the experimental part of the research, we will start from the suggestions offered by the students of the Faculty of Sciences, the University of Craiova (undergraduate cycle, year II) with the purpose to improve online instruction. In this regard, we will use a questionnaire. The designed training model, based on the proposals of the students, will include current training methods, modern instruments, leading to better results in the final evaluation. This aspect will be verified in the final part of the pedagogical experiment, in which we will follow the results of the exam and we will analyze the feedback provided by the students concerning the implementation of their proposals.